Study of the properties of networks of low-dimensional nanomaterials for transparent flexible device applications - Sorel, Sophie (Trinity College (Dublin, Ireland). School of Physics, 2013)
Transparent conductors (TC) - materials that are both transparent and conductive - are of great interest for modern technologies. However, a replacement is needed for the most commonly used TC, Indium tin oxide (ITO), because it requires high temperature processing and lacks flexibility, which is a critical requirement for future applications. Networks of silver nanowires are an excellent candidate for transparent flexible applications. In this work, I made a range of networks - with different thicknesses - of silver nanowires - with different lengths and diameters - in order to understand the effects of the aspect ratio of silver nanowires on the networks' opto-electrical properties.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin